Genetic and Functional Profiling of CD16-Dependent Natural Killer Activation Identifies Patients at Higher Risk of Cardiac Allograft Vasculopathy. Issue 10 (6th March 2018) - Paul, Pascale; Picard, Christophe; Sampol, Emmanuelle; Lyonnet, Luc; Di Cristofaro, Julie; Paul-Delvaux, Louise; Lano, Guillaume; Nicolino-Brunet, Corinne; Ravis, Eleonore; Collart, Frederic; Dignat-George, Francoise; Dussol, Bertrand; et al.
Abstract : Background: Cardiac transplantation is an effective therapy for end-stage heart failure. Because cardiac allograft vasculopathy (CAV) is the major cause of late mortality after heart transplant (HT), there is a need to identify markers that reflect inflammatory or cytotoxic immune mechanisms contributing to its onset. Noninvasive and early stratification of patients at risk remains a challenge for adapting individualized therapy. The CD16 (Fc-gamma receptor 3A [FCGR3A]) receptor was recently identified as a major determinant of antibody-mediated natural killer (NK) cell activation in HT biopsies; however, little is known about the role of CD16 in promoting allograft vasculopathy. This study aimed to investigate whether markers that reflect CD16-dependent circulating NK cell activation may identify patients at higher risk of developing CAV after HT. Methods: Blood samples were collected from 103 patients undergoing routine coronarography angiography for CAV diagnosis (median 5 years since HT). Genomic and phenotypic analyses of FCGR3A/CD16 Fc-receptor profiles were compared in CAV-positive (n=52) and CAV-free patients (n=51). The levels of CD16 expression and rituximab-dependent cell cytotoxic activity of peripheral NK cells in HT recipients were evaluated using a noninvasive NK-cellular humoral activation test. Results: Enhanced levels of CD16 expression and antibody-dependent NK cell cytotoxic function of HT recipients were associated with the FCGR3A-VV genotype. The frequency of the FCGR3A-VV genotype was significantly higher in the CAV + group (odds ratio, 3.9; P =0.0317) than in the CAV - group. The FCGR3A-VV genotype was identified as an independent marker correlated with the presence of CAV at the time of coronary angiography by using multivariate logistic regression models. The FCGR3A-VV genotype was also identified as a baseline-independent predictor of CAV risk (odds ratio, 4.7; P =0.023). Conclusions: This study unravels a prominent role for the CD16-dependent NK cell activation pathway in the complex array of factors that favor the progression of transplant arteriosclerosis. It highlights the clinical potential of a noninvasive evaluation of FCGR3A/CD16 in the early stratification of CAV risk. The recognition of CD16 as a major checkpoint that controls immune surveillance may promote the design of individualized NK cell–targeted therapies to limit vascular damage in highly responsive sensitized patients. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01569334. Abstract : Supplemental Digital Content is available in the text.